Global, regional, and national burden of infertility attributable to polycystic ovary syndrome, 1990–2021: results from the Global Burden of Disease Study 2021 - Liang, Yufan; Zhong, Kexin; Huang, Zhuoyan; Shi, Wenjing; Ou, Yuhua (Frontiers in Public Health, 2025)
BackgroundAnalyzing the temporal trends, inequalities, and predictions of the infertility burden among women of childbearing age due to polycystic ovary syndrome.MethodsWe employed a connection point regression analysis to carefully examine the temporal trends of PCOS-related infertility from 1990 to 2021. An age-period-cohort model was used to assess changes in prevalence across different ages, time periods, and birth cohorts. We also used Bayesian predictive models to forecast future burdens, conducted decomposition analyses to identify key drivers, and assessed health inequalities.ResultsFrom 1990 to 2021, the global age-standardized prevalence rate of PCOS-related infertility increased from 475.54 to 638.15 per 100,000 population, and the years lived with disability (YLDs) increased from 2.77 to 3.67; the number of patients increased from 6.316 million to 12.467 million, with the growth rate of secondary infertility being higher than that of primary infertility. High SDI regions had a high base but showed a slowing growth trend, while middle SDI regions exhibited the fastest “catch-up” growth; East Asia and South Asia ranked among the top in annual growth rate. The global age peak was between 40 and 44 years, with the peak for primary infertility advancing to 20–24 years. It is projected that the number of patients will reach 22.43 million by 2050, of which secondary infertility will account for 82.8%. The absolute gap between high-SDI and low-SDI countries widened, while the relative gap narrowed; the driving factors were mainly Epidemic changes in high SDI regions and population growth in low SDI regions.ConclusionPCOS-related infertility has evolved into a global public health crisis, requiring urgent implementation of precise prevention and control measures based on the life cycle and SDI gradient, as well as promotion of transnational technology sharing and data standardization to avoid its systemic erosion of the reproductive health of the next generation of women.